Is BDNF sufficient for information transfer between microglia and dorsal horn neurons during the onset of central sensitization? - Biggs, James E (BioMed Central, 2010)
Peripheral nerve injury activates spinal microglia. This leads to enduring changes in the properties of dorsal horn neurons that initiate central sensitization and the onset of neuropathic pain. Although a variety of neuropeptides, cytokines, chemokines and neurotransmitters have been implicated at various points in this process, it is possible that much of the information transfer between activated microglia and neurons, at least in this context, may be explicable in terms of the actions of brain derived neurotrophic factor (BDNF). Microglial-derived BDNF mediates central sensitization in lamina I by attenuating inhibitory synaptic transmission. This involves an alteration in the chloride equilibrium potential as a result of down regulation of the potassium-chloride exporter, KCC2. In lamina II, BDNF duplicates many aspects of the effects of chronic constriction injury (CCI) of the sciatic nerve on excitatory transmission. It mediates an increase in synaptic drive to putative excitatory neurons whilst reducing that to inhibitory neurons. CCI produces a specific pattern of changes in excitatory synaptic transmission to tonic, delay, phasic, transient and irregular neurons. A very similar 'injury footprint' is seen following long-term exposure to BDNF. This review presents new information on the action of BDNF and CCI on lamina II neurons, including the similarity of their actions on the kinetics and distributions of subpopulations of miniature excitatory postsynaptic currents (mEPSC). These findings raise the possibility that BDNF functions as a final common path for a convergence of perturbations that culminate in the generation of neuropathic pain.